Modeling the Fate of Escherichia coli O157:H7 and Salmonella enterica in the Agricultural Environment: Current Perspective. Issue 4 (25th March 2014) - Ongeng, Duncan; Haberbeck, Leticia U.; Mauriello, Gianluigi; Ryckeboer, Jaak; Springael, Dirk; Geeraerd, Annemie H.
Abstract The significance of fresh vegetable consumption on human nutrition and health is well recognized. Human infections with Escherichia coli O157:H7 and Salmonella enterica linked to fresh vegetable consumption have become a serious public health problem inflicting a heavy economic burden. The use of contaminated livestock wastes such as manure and manure slurry in crop production is believed to be one of the principal routes of fresh vegetable contamination with E. coli O157:H7 and S. enterica at preharvest stage because both ruminant and nonruminant livestock are known carriers of E. coli O157:H7 and S. enterica in the environment. A number of challenge‐testing studies have examined the fate of E. coli O157:H7 and S. enterica in the agricultural environment with the view of designing strategies for controlling vegetable contamination preharvest. In this review, we examined the mathematical modeling approaches that have been used to study the behavior of E. coli O157:H7 and S. enterica in the manure, manure‐amended soil, and in manure‐amended soil–plant ecosystem during cultivation of fresh vegetable crops. We focused on how the models have been applied to fit survivor curves, predict survival, and assess the risk of vegetable contamination preharvest. The inadequacies of the current modeling approaches are discussed and suggestions for improvements to enhance the applicability of the models as decision tools to control E. coli O157:H7 and S. enterica contamination of fresh vegetables during primary production are presented.